Perovskite oxide/carbon nanotube hybrid bifunctional electrocatalysts for overall water splitting - Wu, X.; Yu, J.; Yang, G.; Liu, H.; Zhou, W.; Shao, Zongping (Pergamon, 2018)
© 2018 Elsevier Ltd Perovskite oxides recently have emerged as efficient electrocatalysts for the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in an alkaline solution. However, most perovskites have poor electrical conductivity at room temperature. Here, to simultaneously enhance the activity and stability towards both OER and HER, we in situ-introduce carbon nanotubes (CNTs) on the perovskite (SrTi0.1Fe0.85Ni0.05O3–d) surface via a simple chemical vapor deposition (CVD) method. First, we evaluate the influence of the CVD temperature on the growth of the CNTs. The optimized electrocatalyst obtained at a temperature of 700 °C (denoted as STFN/CNT-700) exhibits higher OER and HER activities than the bare perovskite, which is reflected by the current density, onset potential, overpotential and Tafel slope, and thus we construct a homemade electrolyzer for overall water splitting using STFN/CNT-700 as both an anode and cathode in alkaline electrolyte. Lastly, the increased performances are mainly attributed to the improved charge transfer process, increased surface area, and synergistic effect between the perovskite phase and the CNTs phase. This work may be inspiring to adjust the performance of metal oxides and prepare highly efficient and low-cost composite electrocatalysts.